A microcrystalline aggregate prepared from multi-component solid waste and its preparation method and application
By selecting solid waste with amorphous structure and fused components, combining wollastonite and calcium feldspar to form a design formula, and performing high temperature sintering, the problem of difficult to improve the strength of artificial aggregates and high water absorption rate is solved, and the problem of the difficulty of improving the strength of artificial aggregates is achieved. High strength, low water absorption and simplified process effects.
Patent Information
- Application Number
- CN202310226824.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-08
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-03-08
AI Technical Summary
When using solid waste to prepare artificial aggregates, it is difficult to simultaneously increase the strength of the aggregate and reduce its water absorption rate. At the same time, the complex process is not conducive to industrial production.
By preferably solid waste with amorphous structure and fusion components, such as magnesium slag, slag and fly ash, the microcrystalline glass phase is prepared according to the composition of wollastonite and calcium feldspar, and sintered at high temperature. High-strength artificial aggregate of the matrix.
It realizes artificial aggregates with high strength and low water absorption, reduces raw material costs and preparation difficulty, simplifies the process flow, and promotes the industrial production of aggregates.
Smart Images

Figure CN116283000B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of building materials, and in particular relates to a microcrystalline aggregate prepared from multi-component solid wastes, and a preparation method and application thereof. Background Art
[0002] Aggregate is an important component of concrete. With the shortage of natural sand and gravel resources and the increasing pressure to deal with large amounts of solid waste, the use of multiple solid wastes to prepare artificial aggregates to replace natural aggregates has become an important trend.
[0003] Chinese invention patent CN202011449619.2 discloses a fly ash artificial aggregate and its preparation method. The raw material composition and formula ratio of the invention are: 5-10 parts of polyvinyl alcohol, 3-5 parts of sodium or potassium compounds, 70-80 parts of fly ash, 7-15 parts of sludge, and the product is obtained after sintering at 1100-1300℃ and cooling in a cooler for 20 minutes. The artificial aggregate prepared by the invention has a bulk density of 450-750kg / m 3 , but the water absorption rate reaches more than 10%, and the compressive strength is only 6.5~8.5MPa.
[0004] Chinese invention patent CN201710204695.9 discloses a method for preparing lightweight artificial aggregate using slag. The raw material composition and formula ratio of the invention are: 60-80 parts of slag, 10-20 parts of carbonized rice husk ash, and 10-20 parts of fly ash. After granulation into balls, sodium bicarbonate solution is sprayed, and finally sintered at 800-1200℃ and naturally cooled to obtain lightweight slag artificial aggregate. The artificial aggregate prepared by the invention has a bulk density of 500kg / m 3 However, the cylinder pressure strength does not exceed 3MPa, and the water absorption rate exceeds 9%. The preparation process is also relatively complicated, which is not conducive to industrial production.
[0005] Chinese invention patent CN101215149A discloses a method for preparing ultra-light artificial aggregate of sludge glass fired at low temperature. The raw material composition and formula ratio of the invention are: 20-70 parts of sludge, 25-75 parts of waste glass powder, and 2-6 parts of auxiliary raw materials. The patent uses waste glass only as a fluxing component, so that the ultra-light artificial aggregate of sludge glass can be prepared at a lower temperature, and the bulk density is 400g / cm 3 , but its cylinder pressure strength is only about 1MPa, and its water absorption rate is over 6%.
[0006] Chinese invention patent CN202210072395.0 discloses a lightweight, high-strength artificial aggregate based on a microcrystalline glass phase and its preparation method. The raw material composition and formula ratio of the invention are: 50-70 parts of construction slag, 20-40 parts of glass, 5 parts of calcium carbonate, 5 parts of light magnesium oxide and 2-10 parts of nucleating agent (calcium fluoride, titanium dioxide or chromium trioxide). The artificial aggregate prepared by the invention has a bulk density of 500-600kg / m 3 , the compressive strength reaches more than 10MPa, and the water absorption rate is less than 1%. However, a certain amount of analytical pure reagents are introduced into the raw materials as correction raw materials (calcium carbonate and light magnesium oxide), and the heating rate is slow in the preparation process of artificial aggregates, and there is a 1h pre-sintering at 800℃ and a 1h roasting at the roasting temperature. The preparation process is slightly complicated, so it is difficult to realize industrial production.
[0007] In summary, the current problems of using solid waste to produce artificial aggregates are as follows:
[0008] (1) In the research on preparing artificial aggregates from solid waste, more emphasis is placed on how to reduce the density of artificial aggregates, while there is a lack of attention paid to the water absorption rate and strength properties of artificial aggregates.
[0009] (2) In the production of artificial aggregates from solid waste, the chemical composition and structural characteristics of different solid wastes are not fully utilized, and there is a lack of selection and control of the artificial aggregate matrix crystals, which limits the performance of the prepared artificial aggregate.
[0010] (3) The preparation of high-strength aggregates is often more complicated in terms of raw material composition, and some admixture components may even be added to improve the performance of the aggregates. In addition, the roasting process of high-quality aggregates may be more complicated. The above shortcomings may be unfavorable for the industrial production of the aggregates. Summary of the invention
[0011] In view of the shortcomings of the prior art, the purpose of the present invention is to propose a microcrystalline aggregate prepared from multi-solid waste and its preparation method and application. The present invention aims to provide an easy-to-implement method for preparing high-strength, low-water absorption artificial aggregate and a formula design scheme to solve the technical problems of difficulty in improving the strength of artificial aggregate and high water absorption. In addition, the process flow is optimized to reduce the cost and difficulty of preparing the high-quality aggregate of the present invention, laying a certain foundation for the industrial preparation of aggregates.
[0012] The purpose of the present invention is to fully optimize solid wastes with amorphous structure (preparation of microcrystalline phase) properties and flux components (CaO, Na2O, K2O), design a formula according to the composition of wollastonite and anorthite, and achieve it through high-temperature sintering.
[0013] Based on the above-mentioned inventive ideas, the solid waste of the present invention patent is scientifically selected. The specific description is as follows: magnesium slag is the waste slag produced in the Pijiang magnesium smelting process. Among them, it contains a large amount of CaO, which can be used as a fluxing component to significantly reduce the roasting temperature of artificial aggregates, and provide Ca elements for the microcrystalline glass phase, as a source component of the microcrystalline ceramic glass phase. Slag is a by-product of the blast furnace ironmaking process, in which the content of CaO, SiO2 and Al2O3 accounts for more than 90%, and the structure has a highly active amorphous structure. Similar to magnesium slag, it can play a role in fluxing and providing Ca elements in the preparation process of artificial aggregates. In addition, its amorphous structure can also serve as a precursor for crystal precipitation, promote the formation of the target crystal phase, and improve the strength of artificial aggregates.
[0014] Fly ash is the main solid waste discharged from coal-fired power plants, mainly composed of Si and Al elements. In addition, most of the fly ash is composed of highly active amorphous substances, which is conducive to the formation of liquid phase and the precipitation of new phase crystals in the roasting process of artificial aggregates.
[0015] Construction waste is a typical solid waste generated in large-scale urban construction projects. However, its composition is similar to that of natural raw material clay for aggregate production, and it has good bonding properties, so it can act as a binder in the mixture without the need for additional cementing components.
[0016] The purpose of the present invention is achieved through the following technical solutions:
[0017] A microcrystalline aggregate prepared from multi-solid wastes is prepared by taking wollastonite microcrystalline glass phase as a matrix and comprising the following components in parts by weight: 30 to 50 parts of waste glass, 25 to 45 parts of construction slag, 15 to 35 parts of magnesium slag and 2 to 10 parts of nucleating agents; or by taking calcium feldspar microcrystalline glass phase as a matrix and comprising the following components in parts by weight: 40 to 60 parts of slag powder, 20 to 40 parts of construction slag, 10 to 30 parts of fly ash and 2 to 10 parts of nucleating agents.
[0018] Preferably, the engineering slag is brown block slag produced during the underground development project, which is broken up and then dried at 105° C. for 48 hours before use.
[0019] Preferably, the slag powder is a by-product of blast furnace ironmaking and is a white powder obtained after a refinement process.
[0020] Preferably, the fly ash is gray powder discharged from the combustion of coal in a coal-fired power plant.
[0021] Preferably, the waste glass is discarded colorless transparent flat glass.
[0022] Preferably, the magnesium slag is granular or blocky grey waste slag produced in the Pijiang magnesium smelting process.
[0023] Preferably, the nucleating agent is one of calcium fluoride, titanium dioxide and chromium trioxide.
[0024] Preferably, the nucleating agent is of analytical grade.
[0025] A method for preparing microcrystalline aggregate using multi-component solid waste comprises the following steps:
[0026] (1) respectively drying, crushing, ball-milling, and sieving construction slag, waste glass, magnesium slag, fly ash, slag powder, and nucleating agent to obtain waste glass powder, construction slag powder, magnesium slag powder, fly ash, slag powder, and nucleating agent powder;
[0027] (2) The waste glass powder, construction slag powder, magnesium slag powder, fly ash, slag powder and nucleating agent powder described in step (1) are weighed according to the material formula, mixed to obtain a mixture, and 30-40% of water by weight of the mixture is added and stirred to obtain a batch material. The batch material is granulated, dried and sintered to obtain the microcrystalline aggregate prepared from multi-solid waste.
[0028] Preferably, in the engineering slag in step (1), the SiO2 content is 40-70wt%, the Al2O3 content is 10-30wt%, and the Fe2O3 content is 0-10wt%.
[0029] Preferably, in the waste glass of step (1), the SiO2 content is 60-80wt%, the CaO content is 5-15wt%, the MgO content is 3-10wt%, and the Na2O content is 10-20wt%.
[0030] Preferably, in the magnesium slag of step (1), the SiO2 content is 20-40wt%, the Fe2O3 content is 2-10wt%, the CaO content is 40-60wt%, and the MgO content is 5-20wt%.
[0031] Preferably, in the fly ash of step (1), the SiO2 content is 40-65wt%, the Al2O3 content is 20-40wt%, and the Fe2O3 content is 2-10wt%.
[0032] Preferably, in the slag of step (1), the SiO2 content is 25-50wt%, the Al2O3 content is 5-25wt%, and the CaO content is 30-50wt%.
[0033] Preferably, the drying temperature in step (1) is 105° C. and the drying time is 48 h.
[0034] Preferably, the sieving in step (1) is through a 200-mesh sieve.
[0035] Preferably, the granulation method in step (2) is: granulation and molding by a granulator to obtain spherical balls with a particle size of 10 to 12 mm.
[0036] Preferably, the drying temperature in step (2) is 105° C. and the drying time is 2 to 4 hours.
[0037] Preferably, the sintering method in step (2) is:
[0038] Heating stage: heating from room temperature to 600°C at a heating rate of 5-10°C / min;
[0039] Nucleation stage: keep at 600℃ for 5-15min;
[0040] Heating stage:
[0041] Using wollastonite glass-ceramics as the matrix: heating from 600°C to 1020-1100°C at a heating rate of 5-15°C / min;
[0042] Taking calcium feldspar microcrystalline glass phase as the matrix: heating from 600°C to 1120-1200°C at a heating rate of 5-15°C / min;
[0043] Sintering stage:
[0044] Using wollastonite glass-ceramic phase as the matrix: keeping at 1040-1100°C for 10-30 minutes and then cooling to room temperature with the furnace;
[0045] With calcium feldspar microcrystalline glass phase as the matrix: keep warm at 1170-1200℃ for 10-30min and then cool to room temperature with the furnace.
[0046] The above-mentioned microcrystalline aggregate prepared from multi-solid waste is used in the preparation of concrete.
[0047] Compared with the prior art, the beneficial effects of the present invention include:
[0048] The present invention provides a method for firing high-strength glass-ceramic phase artificial aggregate using a variety of solid wastes. On the one hand, the goal of common resource treatment of a variety of solid wastes is achieved, and the raw material source is abundant and the cost is low; on the other hand, the performance of artificial aggregates is significantly improved by making full use of the high degree of glass-ceramic phase, high hardness, low water absorption rate, good chemical stability and thermal stability, etc., and the strength of artificial aggregates is greatly improved and the water absorption rate is reduced. In addition, the present invention refers to the traditional process of preparing aggregates by rotary kilns in the preparation process, and the preparation process is shorter and easier to achieve industrial application.
[0049] Traditional architectural glass-ceramics often need to be melted at high temperature (usually 1500℃, 2-4h) to clarify and anneal the base glass, then renucleate (600-700℃, 2-4h) and crystallize (900-1100℃, 2-4h) to prepare glass-ceramics. The patent of this invention utilizes the properties of amorphous structure (preparation of microcrystalline phase) and fluxing components (CaO, Na2O, K2O) in solid waste, and the crystallization process is completed quickly at low temperature (1100℃) in a short time. The process is simple and convenient for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 This is the internal microscopic morphology of the microcrystalline aggregate prepared in Example 2.
[0051] Figure 2 This is the internal microscopic morphology of the microcrystalline aggregate prepared in Example 1.
[0052] Figure 3 This is the internal microscopic morphology of the high-strength artificial aggregate with calcium feldspar microcrystalline glass phase as the matrix as described in Comparative Example 4.
[0053] Figure 4 This is the internal microscopic morphology of the microcrystalline aggregate prepared in Example 4.
[0054] Figure 5 This is the internal microscopic morphology of the high-strength artificial aggregate of engineering slag prepared in Comparative Example 2.
[0055] Figure 6 The present invention is a process flow chart for preparing microcrystalline aggregate.
[0056] Figure 7 This is the XRD pattern of the microcrystalline aggregate prepared in Example 1.
[0057] Figure 8 This is the XRD spectrum of the microcrystalline aggregate prepared in Example 4.
[0058] Fig. 9 This is the XRD spectrum of the high-strength artificial aggregate of engineering slag prepared in Comparative Example 2. DETAILED DESCRIPTION
[0059] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0060] Example 1
[0061] A microcrystalline aggregate prepared from multi-component solid waste, with wollastonite microcrystalline glass phase as the matrix, is prepared by the following steps:
[0062] (1) Preparation of raw materials: First, crush the construction waste soil and magnesium slag and place them in an oven at 105°C to dry for 48 hours. Then, crush the waste glass (transparent flat glass), construction waste soil, magnesium slag and nucleating agent analytical pure CaF2 separately, ball-mill and pass through a 200-mesh sieve to obtain a powder with a residue of less than 5%. Then, according to the mass ratio, take waste glass: construction waste soil: magnesium slag: calcium fluoride = 35:40:25:2;
[0063] (2) Raw material mixing, raw material ball forming and drying: Put all raw materials into a mixing tank and mix them in a mixer at a speed of 120r / min for 4 hours to obtain a raw material mixture; then add tap water accounting for 30-40% of the raw material mixture to the raw material mixture, and form it into balls with a diameter of 10-12mm in a granulator. Put the balls in an oven and dry them at 105°C for 4 hours to obtain dry artificial aggregate raw material balls;
[0064] (3) Calcination of artificial aggregate: The raw material balls of artificial aggregate are placed in a muffle furnace and calcined according to the following calcination system: the temperature is increased from room temperature to 600°C at a heating rate of 10°C / min, and kept at 600°C for 10 min, then the temperature is increased from 600°C to 1080°C at a heating rate of 10°C / min, and kept at 1080°C for 30 min, and then naturally cooled to room temperature to obtain the product.
[0065] Example 1 obtained an apparent density of 1480 kg / m 3 (Bulk density about 700kg / m 3 ), 24h water absorption rate is 0.90%, and single particle compressive strength reaches 14.84MPa (here is the calculated average value, the experimental data comes from 10 artificial aggregates of similar size and regular shape, and their strength average value is calculated).
[0066] Example 2
[0067] A microcrystalline aggregate prepared from multi-component solid waste, with wollastonite microcrystalline glass phase as the matrix, is prepared by the following steps:
[0068] (1) Preparation of raw materials: First, crush the construction waste soil and magnesium slag and place them in an oven at 105°C to dry for 48 hours. Then, crush the waste glass (transparent flat glass), construction waste soil, magnesium slag and nucleating agent analytical pure CaF2 separately, ball-mill and pass through a 200-mesh sieve to obtain a powder with a residue of less than 5%. Then, according to the mass ratio, take waste glass: construction waste soil: magnesium slag: calcium fluoride = 35:40:25:2;
[0069] (2) Raw material mixing, raw material ball forming and drying: Put all raw materials into a mixing tank and mix them in a mixer at a speed of 120r / min for 4 hours to obtain a raw material mixture; then add tap water accounting for 30-40% of the raw material mixture to the raw material mixture, and form it into balls with a diameter of 10-12mm in a granulator. Put the balls in an oven and dry them at 105°C for 4 hours to obtain dry artificial aggregate raw material balls;
[0070] (3) Calcination of artificial aggregate: The raw material balls of artificial aggregate are placed in a muffle furnace and calcined according to the following calcination system: the temperature is increased from room temperature to 600°C at a heating rate of 10°C / min, and kept at 600°C for 10 min, then the temperature is increased from 600°C to 1040°C at a heating rate of 10°C / min, and kept at 1040°C for 30 min, and then naturally cooled to room temperature to obtain the product.
[0071] Example 2 obtained an apparent density of 1990 kg / m 3 (Bulk density about 900kg / m 3 ), 24h water absorption rate is 0.99%, and single particle compressive strength reaches 28.41MPa of artificial aggregate (here is the calculated average value, the experimental data comes from 10 artificial aggregates of similar size and regular shape, and their strength average value is calculated).
[0072] Example 3
[0073] A microcrystalline aggregate prepared from multi-component solid waste, with calcium feldspar microcrystalline glass phase as the matrix, is prepared by the following steps:
[0074] (1) Preparation of raw materials: First, crush the construction slag and slag and place them in an oven at 105°C to dry for 48 hours. Then, crush and ball-mill the fly ash, construction slag, slag and nucleating agent analytical pure CaF2 and pass through a 200 mesh sieve with a residue of less than 5%. Then, mix them according to the mass ratio of construction slag: fly ash: slag: calcium fluoride = 30:20:50:2;
[0075] (2) Raw material mixing, raw material ball forming and drying: Put all raw materials into a mixing tank and mix them in a mixer at a speed of 120r / min for 4 hours to obtain a raw material mixture; then add tap water accounting for 30-40% of the raw material mixture to the raw material mixture, and form it into balls with a diameter of 10-12mm in a granulator. Put the balls in an oven and dry them at 105°C for 4 hours to obtain dry artificial aggregate raw material balls;
[0076] (3) Calcination of artificial aggregate: The raw material balls of artificial aggregate are placed in a muffle furnace and calcined according to the following calcination system: the temperature is increased from room temperature to 600°C at a heating rate of 10°C / min, and kept at 600°C for 10 min, then the temperature is increased from 600°C to 1170°C at a heating rate of 10°C / min, and kept at 1170°C for 30 min, and then naturally cooled to room temperature to obtain the product.
[0077] Example 3: The apparent density is 2200 kg / m 3 , 24h water absorption rate is 1.64%, and the single particle compressive strength reaches 39.95MPa of artificial aggregate (here is the calculated average value, the experimental data comes from 10 artificial aggregates of similar size and regular shape, and their strength average value is calculated).
[0078] Example 4
[0079] A microcrystalline aggregate prepared from multi-component solid waste, with calcium feldspar microcrystalline glass phase as the matrix, is prepared by the following steps:
[0080] (1) Preparation of raw materials: First, crush the construction slag and slag and place them in an oven at 105°C to dry for 48 hours. Then, crush and ball-mill the fly ash, construction slag, slag and nucleating agent analytical pure CaF2 and pass through a 200 mesh sieve with a residue of less than 5%. Then, mix them according to the mass ratio of construction slag: fly ash: slag: calcium fluoride = 30:20:50:2;
[0081] (2) Raw material mixing, raw material ball forming and drying: Put all raw materials into a mixing tank and mix them in a mixer at a speed of 120r / min for 4 hours to obtain a raw material mixture; then add tap water accounting for 30-40% of the raw material mixture to the raw material mixture, and form it into balls with a diameter of 10-12mm in a granulator. Put the balls in an oven and dry them at 105°C for 4 hours to obtain dry artificial aggregate raw material balls;
[0082] (3) Calcination of artificial aggregate: The raw material balls of artificial aggregate are placed in a muffle furnace and calcined according to the following calcination system: the temperature is increased from room temperature to 600°C at a heating rate of 10°C / min, and kept at 600°C for 10 min, then the temperature is increased from 600°C to 1200°C at a heating rate of 10°C / min, and kept at 1200°C for 30 min, and then naturally cooled to room temperature to obtain the product.
[0083] Example 4: The apparent density is 1900 kg / m 3 , 24h water absorption rate is 0.25%, and the single particle compressive strength reaches 39.28MPa of artificial aggregate (here is the calculated average value, the experimental data comes from 10 artificial aggregates of similar size and regular shape, and their strength average value is calculated).
[0084] Comparative Example 1
[0085] A method for preparing high-strength artificial aggregate from engineering slag, comprising the following steps:
[0086] (1) Preparation of raw materials: First, the construction waste soil is crushed and placed in an oven at 105°C for 48 hours. Then, the construction waste soil is crushed, ball-milled, and passed through a 200-mesh sieve to obtain a powder raw material with a sieve residue of less than 5%.
[0087] (2) Forming and drying of raw material balls: Add tap water accounting for 30-40% of the raw material to the raw material, and form the raw material balls with a diameter of 10-12 mm through a granulator. Put the raw material balls in an oven and dry them at 105°C for 4 hours to obtain dry artificial aggregate raw material balls;
[0088] (3) Calcination of artificial aggregate: The raw material balls of artificial aggregate are placed in a muffle furnace and calcined according to the following calcination system: the temperature is increased from room temperature to 600°C at a heating rate of 10°C / min, and kept at 600°C for 10 min, then the temperature is increased from 600°C to 1160°C at a heating rate of 10°C / min, and kept at 1160°C for 30 min, and then naturally cooled to room temperature to obtain the product.
[0089] Comparative Example 1 obtained an apparent density of 2120 kg / m 3 , 24h water absorption rate is 0.14%, and single particle compressive strength is 22.2MPa of artificial aggregate (here is the calculated average value, the experimental data comes from 10 artificial aggregates of similar size and regular shape, and their strength average value is calculated).
[0090] Comparative Example 2
[0091] A method for preparing high-strength artificial aggregate from engineering slag, comprising the following steps:
[0092] (1) Preparation of raw materials: First, the construction waste soil is crushed and placed in an oven at 105°C for 48 hours. Then, the construction waste soil is crushed, ball-milled, and passed through a 200-mesh sieve to obtain a powder raw material with a sieve residue of less than 5%.
[0093] (2) Forming and drying of raw material balls: Add tap water accounting for 30-40% of the raw material to the raw material, and form the raw material balls with a diameter of 10-12 mm through a granulator. Put the raw material balls in an oven and dry them at 105°C for 4 hours to obtain dry artificial aggregate raw material balls;
[0094] (3) Calcination of artificial aggregate: The raw material balls of artificial aggregate are placed in a muffle furnace and calcined according to the following calcination system: the temperature is increased from room temperature to 600°C at a heating rate of 10°C / min, and kept at 600°C for 10 min, then the temperature is increased from 600°C to 1220°C at a heating rate of 10°C / min, and kept at 1220°C for 30 min, and then naturally cooled to room temperature to obtain the product.
[0095] Comparative Example 2 obtained an apparent density of 1450 kg / m 3 , 24h water absorption rate is 1.50%, and single particle compressive strength is 9.6MPa of artificial aggregate (here is the calculated average value, the experimental data comes from 10 artificial aggregates of similar size and regular shape, and their strength average value is calculated).
[0096] Comparative Example 3
[0097] The product is prepared by Example 1 in the specification of the Chinese invention patent "A lightweight and high-strength ceramsite based on microcrystalline glass phase and its preparation method and application" with application number CN202210072395.0.
[0098] Comparative Example 4
[0099] A method for preparing a high-strength artificial aggregate with anorthite microcrystalline glass phase as a matrix, comprising the following steps:
[0100] (1) Preparation of raw materials: First, crush the construction slag and slag and place them in an oven at 105°C for 48 hours. Then, crush and ball-mill the fly ash, construction slag, slag and nucleating agent analytical pure CaF2 and pass through a 200 mesh sieve with a residue of less than 5%. Then, mix them according to the mass ratio of construction slag: fly ash: slag: calcium fluoride = 30:20:50:2;
[0101] (2) Raw material mixing, raw material ball forming and drying: Put all raw materials into a mixing tank and mix them in a mixer at a speed of 120r / min for 4 hours to obtain a raw material mixture; then add tap water accounting for 30-40% of the raw material mixture to the raw material mixture, and form it into balls with a diameter of 10-12mm in a granulator. Put the balls in an oven and dry them at 105°C for 4 hours to obtain dry artificial aggregate raw material balls;
[0102] (3) Calcination of artificial aggregate: The raw material balls of artificial aggregate are placed in a muffle furnace and calcined according to the following calcination schedule: the temperature is increased from room temperature to 600°C at a heating rate of 10°C / min, and kept at 600°C for 10 min, then the temperature is increased from 600°C to 1150°C at a heating rate of 10°C / min, and kept at 1150°C for 30 min, and then naturally cooled to room temperature to obtain the product.
[0103] Comparative Example 4 obtained an apparent density of 2070 kg / m 3 , 24h water absorption rate is 6.02%, and the single particle compressive strength reaches 27.38MPa of artificial aggregate (here is the calculated average value, the experimental data comes from 10 artificial aggregates of similar size and regular shape, and their strength average value is calculated).
[0104] Under the condition of 1150℃, the calcination temperature is low, the liquid viscosity is high and the liquid volume is insufficient, and the growth of ceramsite crystals is not obvious (see Figure 4 ), there are more glass phases, so its strength still has room for improvement. On the other hand, the ceramsite has not formed a sufficient enamel layer on the outside, and the water absorption rate is high.
[0105] Comparative Example 5
[0106] A method for preparing a high-strength artificial aggregate with anorthite microcrystalline glass phase as a matrix, comprising the following steps:
[0107] (1) Preparation of raw materials: First, crush the construction slag and slag and place them in an oven at 105°C for 48 hours. Then, crush and ball-mill the fly ash, construction slag, slag and nucleating agent analytical pure CaF2 and pass through a 200 mesh sieve with a residue of less than 5%. Then, mix them according to the mass ratio of construction slag: fly ash: slag: calcium fluoride = 30:20:50:2;
[0108] (2) Raw material mixing, raw material ball forming and drying: Put all raw materials into a mixing tank and mix them in a mixer at a speed of 120r / min for 4 hours to obtain a raw material mixture; then add tap water accounting for 30-40% of the raw material mixture to the raw material mixture, and form it into balls with a diameter of 10-12mm in a granulator. Put the balls in an oven and dry them at 105°C for 4 hours to obtain dry artificial aggregate raw material balls;
[0109] (3) Calcination of artificial aggregate: The raw material balls of artificial aggregate are placed in a muffle furnace and calcined according to the following calcination schedule: the temperature is increased from room temperature to 600°C at a heating rate of 10°C / min, and kept at 600°C for 10 min, then the temperature is increased from 600°C to 1220°C at a heating rate of 10°C / min, and kept at 1220°C for 30 min, and then naturally cooled to room temperature to obtain the product.
[0110] The aggregate obtained in Comparative Example 5 collapsed and deformed due to the high calcination temperature and low liquid viscosity, and could not be used in practice.
[0111] Table 1 is a statistical table of the preparation processes, raw materials and various properties of Examples 1 to 4 and Comparative Examples 2 to 4.
[0112] Table 1 Comparison of preparation process, raw materials and density strength of the embodiments and comparative examples
[0113]
[0114]
[0115] Studies have shown that the best calcination temperature for calcium feldspar aggregate is 1170-1200°C. The best calcination temperature for wollastonite aggregate is 1040-1100°C.
[0116] As shown in Table 1, compared with Comparative Example 2, Example 1 and Example 2 have higher strength under similar density conditions, and compared with Comparative Example 3, Example 1 and Example 2 are simpler in the sintering process.
[0117] Figure 1 The internal microscopic morphology of the microcrystalline aggregate prepared in Example 2 is shown in FIG. Figure 1 It can be seen that the wollastonite inside the wollastonite aggregate grows into fine needles.
[0118] Figure 2 The internal microscopic morphology of the microcrystalline aggregate prepared in Example 1 is shown in FIG. Figure 2 It can be seen that the wollastonite inside the wollastonite aggregate grows into long columns and interweaves with each other inside the aggregate.
[0119] Figure 3 This is the internal microscopic morphology of the high-strength artificial aggregate based on calcium feldspar microcrystalline glass phase described in Comparative Example 4. Figure 3 It can be seen that the short columnar calcium feldspar inside the calcium feldspar aggregate gradually precipitates from the glass phase.
[0120] Figure 4 The internal microscopic morphology of the microcrystalline aggregate prepared in Example 4 is shown in FIG. Figure 4 It can be seen that the short columnar calcium feldspar in the calcium feldspar aggregate has prominent outlines and is intertwined with each other. The aggregate has a good crystallization effect and it is difficult to find the non-crystallized glass phase.
[0121] Figure 5 The internal microscopic morphology of the high-strength artificial aggregate of engineering slag prepared in Comparative Example 2 is shown in FIG. Figure 5 It can be seen that the crystallization effect of slag aggregate is not obvious, and its microstructure is composed of a large amount of glass phase and a small amount of granular quartz.
[0122] Figure 6 The process flow chart of preparing microcrystalline aggregate of the present invention is as follows: Figure 6 It can be seen that the entire process is very simple.
[0123] Figure 7 The XRD pattern of the microcrystalline aggregate prepared in Example 1 is Figure 7It can be seen that the crystal phase composition of wollastonite aggregate is basically wollastonite.
[0124] Figure 8 The XRD pattern of the microcrystalline aggregate prepared in Example 4 is as follows: Figure 8 It can be seen that the crystal phase composition of calcium feldspar aggregate is basically calcium feldspar.
[0125] Fig. 9 The XRD pattern of the high-strength artificial aggregate of engineering slag prepared in Comparative Example 2 is shown in FIG. Fig. 9 It can be seen that the crystal phase composition of slag aggregate is mainly quartz crystal.
[0126] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A microcrystalline aggregate prepared from multi-component solid waste, characterized in that: The wollastonite microcrystalline glass phase is used as a matrix, and the following components are prepared by weight: 35 parts of waste glass, 40 parts of construction slag, 25 parts of magnesium slag and 2 parts of nucleating agent; the nucleating agent is one of calcium fluoride, titanium dioxide and chromium trioxide; the preparation method of the microcrystalline phase aggregate prepared from multi-component solid waste comprises the following steps: (1) The construction waste soil, waste glass, magnesium slag and nucleating agent are dried, crushed, ball-milled and sieved to obtain waste glass powder, construction waste soil powder, magnesium slag powder and nucleating agent powder; (2) the waste glass powder, construction slag powder, magnesium slag powder and nucleating agent powder described in step (1) are weighed according to the formula, mixed to obtain a mixture, 30-40% of water by weight of the mixture is added and stirred to obtain a batch material, and the batch material is granulated, dried and sintered to obtain the microcrystalline aggregate prepared from multi-component solid waste; The sintering method in step (2) is: Heating stage: heating from room temperature to 600°C at a heating rate of 5-10°C / min; Nucleation stage: keep at 600℃ for 5~15min; Heating stage: The temperature was raised from 600°C to 1040°C at a heating rate of 5-15°C / min; Sintering stage: After keeping at 1040℃ for 30min, cool to room temperature in the furnace.
2. A microcrystalline aggregate prepared from multi-component solid waste, characterized in that: The calcium feldspar microcrystalline glass phase is used as a matrix, and the following components are prepared by weight: 40-60 parts of slag powder, 20-40 parts of engineering slag, 10-30 parts of fly ash and 2-10 parts of nucleating agent; the nucleating agent is one of calcium fluoride, titanium dioxide and chromium trioxide; the preparation method of the microcrystalline phase aggregate prepared from multi-component solid waste comprises the following steps: (1) The construction slag, slag powder, fly ash and nucleating agent are dried, crushed, ball-milled and sieved to obtain construction slag powder, slag powder, fly ash and nucleating agent powder; (2) The construction slag powder, slag powder, fly ash and nucleating agent powder described in step (1) are weighed according to the formula, mixed to obtain a mixture, and 30-40% of water by weight of the mixture is added and stirred to obtain a batch material. The batch material is granulated, dried and sintered to obtain the microcrystalline aggregate prepared from multi-component solid waste; The sintering method in step (2) is: Heating stage: heating from room temperature to 600°C at a heating rate of 5-10°C / min; Nucleation stage: keep at 600℃ for 5~15min; Heating stage: The temperature was raised from 600°C to 1170~1200°C at a heating rate of 5~15°C / min; Sintering stage: Keep at 1170~1200℃ for 10~30min and then cool to room temperature with the furnace.
3. The microcrystalline aggregate prepared from multi-component solid waste according to claim 1, characterized in that: In the engineering slag of step (1), the content of SiO2 is 40-70wt%, the content of Al2O3 is 10-30wt%, and the content of Fe2O3 is 0-10wt%; In the waste glass of step (1), the content of SiO2 is 60-80wt%, the content of CaO is 5-15wt%, the content of MgO is 3-10wt%, and the content of Na2O is 10-20wt%; In the magnesium slag of step (1), the SiO2 content is 20-40wt%, the Fe2O3 content is 2-10wt%, the CaO content is 40-60wt%, and the MgO content is 5-20wt%.
4. The microcrystalline aggregate prepared from multi-component solid waste according to claim 2, characterized in that: In the engineering slag of step (1), the content of SiO2 is 40-70wt%, the content of Al2O3 is 10-30wt%, and the content of Fe2O3 is 0-10wt%; In the fly ash of step (1), the content of SiO2 is 40-65wt%, the content of Al2O3 is 20-40wt%, and the content of Fe2O3 is 2-10wt%; In the slag of step (1), the SiO2 content is 25-50wt%, the Al2O3 content is 5-25wt%, and the CaO content is 30-50wt%.
5. The microcrystalline aggregate prepared from multi-component solid waste according to claim 1 or 2, characterized in that: The drying temperature in step (1) is 105° C. and the drying time is 48 h.
6. The microcrystalline aggregate prepared from multi-component solid waste according to claim 1 or 2, characterized in that: The drying temperature in step (2) is 105° C. and the drying time is 2 to 4 hours.
7. The microcrystalline aggregate prepared from multi-component solid waste according to claim 1 or 2, characterized in that: The granulation method of step (2) is: granulation and molding by a granulator to obtain spherical balls with a particle size of 10-12 mm.
8. The microcrystalline aggregate prepared from multi-component solid waste according to claim 7, characterized in that: The sieving in step (1) is through a 200-mesh sieve.
9. Use of the microcrystalline aggregate prepared from multi-solid waste as claimed in claim 1 or 2 in preparing concrete.
Citation Information
Patent Citations
Low-temperature burning method for sludge glass ultra-light haydite
CN101215149A
Method of preparing light ceramisite by use of muck
CN107021775A
Fly ash ceramsite and preparation method thereof
CN112552021A
A lightweight, high-strength ceramic particle with a microcrystalline glass phase as its matrix, its preparation method, and its application.
CN114409258B
High-strength porous thermal-insulation ceramsite prepared by compounding high-content manganese slag with muck and coal-series waste and preparation method of high-strength porous thermal-insulation ceramsite
CN113800948A